Izgradnja pravne države u Bosni i Hercegovini / Developing the Rule of Law in Bosnia and Herzegovina - Čizmić, Mirsad; Neretljak, Hamdija (Pregled: časopis za društvena pitanja / Periodical for social issues, 2016)
When we talk about the concept of the Rule of Law, it usually refers to a state where constitutional rights and freedoms of man and citizen are generally observed, which in addition, respects the principles of constitutionality and legality, in which the courts are independent from the influence of other levels of government and political structures, the state in which it operates separation of power, and in which all holders of government functions are politically and legally responsible-for such a state is said to have embraced the rule of law. The paper is divided into three parts. The first part of the paper discusses general State and Law, where we define the concept of the state, the concept of rights, and the rule of law. The second part is devoted to the democratic constitutional state. The third part of the paper discusses Bosnia and Herzegovina as a state of law within which we talk about the state-legal order of Bosnia and Herzegovina, constitutional features of the entity, the legislative and executive authorities, human rights and political crisis in Bosnia and Herzegovina. This is followed by the concluding remarks.